Gerald's game [compact disc, unabridged] - King, Stephen, 1947- (HighBridge Audio, 2008)
Gerald Burlingame and his wife Jessie have been married for twenty years and together have always been into kinky sex. But one night during a handcuffed midnight rendezvous Jessie finds herself trapped under her husband's corpse. With Jessie's troubling past she must find a way out before the police arrive and things really start to get out of hand.